Kegiatan Kompetisi Olah Raga Mahasiswa Antar Fakultas Sportavest 2023 Untuk Pemberdayaan UMKM di Kelurahan Pondok Labu - Afif Amir Amrullah; Cahya Arbitera (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
One of the tridharmas goals for higher education is the existence of a campus can provide benefits and prosperity to society. After the Covid-19 pandemic, there was a slowdown in people's economic activities, marked by a large number of unemployed people and a decrease in purchasing power, as well as a reduction in the income of MSMEs (UMKM) in the area around the UPN Veteran Jakarta campus. If this conditionremain ignored, it will lead to a negativeimpact and reduce social relations between campus residentsandsurrounding residents. Because efforts areneeded to improve campus relations with local residents while empowering the economy through Sportavest 2023 activities. This research containsservice activities regarding empoweringcommunity MSMEs in Pondok Labu Subdistrict to be able to promote their products widely and increase income from product sales which synergized with sports activities from student.